Measuring speed of vessels operating around endangered southern resident killer whales (Orcinus orca) in Salish Sea critical habitat. (January 2022) - Lo, Catherine F.; Nielsen, Kimberly A.; Ashe, Erin; Bain, David E.; Mendez-Bye, Andrea; Reiss, Stephanie A.; Bogaard, Laura T.; Collins, Marena Salerno; Williams, Rob
Abstract: Motorized vessels are a major source of anthropogenic noise and can have adverse effects on species relying on sound for communication and feeding. Monitoring noise levels received by endangered southern resident killer whales (SRKWs) requires knowing the number, distance, and speed of surrounding vessels, including small boats that do not have Automatic Identification Systems (AIS). A method for estimating their speed is required to predict received noise levels and compliance with vessel regulations. We compared theodolite and photogrammetry methods to estimate the number, distance, and speed of vessels in SRKW Salish Sea summertime critical habitat. By treating AIS as "truth", we found photogrammetry-derived ranges and speeds were more variable than theodolite estimates. Error in photogrammetry-derived speeds increased with range. Overall, we found time saved in the field using photogrammetry was more than offset by long analysis time. Theodolite data were relatively easy to collect, and produced accurate and precise results. Highlights: Anthropogenic noise affects vocalizing species like southern resident killer whales. Sound models exclude small vessels without an Automatic Identification System. Boat number, distance, and speed are required to monitor received noise levels. We compared theodolite and photogrammetry to Automatic Identification System data. Range and speed estimates from theodolite were more accurate than photogrammetry.